ZIF‐8 Decorated WO3 Nanoplates with Robust Surface Activation for the Enhanced Performances in Photocatalytic N2 Fixation. Issue 22 (10th June 2021) - Xu, Fang; Pan, Jialiang; Li, Bian; Wu, Dapeng; Wang, Xinjun; Jiang, Yuqin; Li, Wei; Jiang, Kai; Niu, Bingxuan
Abstract: In order to achieve the activation of the inert N≡N triple bonds during the photo‐derived N2 fixation, WO3 /ZIF‐8 heterogeneous materials with controlled ZIF‐8 coating layer on WO3 nanoplates were prepared via a facile wet process. The WO3 /ZIF‐8 heterogeneous materials were adopted as photocatalysts in the conversion from N2 to nitrate under visible light irradiation. The results demonstrated that WO3 /ZIF‐8 heterogeneous materials has NO 3− yield of ∼5.4 mg/g, which is ∼5 times higher than that of WO3 nanoplates (∼1.1 mg/g). The improved photocatalytic performance of WO3 /ZIF‐8 heterogeneous materials was attributed to the enhanced physical and chemical adsorption of N2 molecules resulting from the porous structure of ZIF‐8. In addition, WO3 /ZIF‐8 heterogeneous materials exhibited enhanced separation and transfer of photogenerated electron‐hole pairs due to the optimized interface between WO3 and ZIF‐8, which finally contributed to the high performances in the photocatalytic N2 fixation. Abstract : WO3 /ZIF‐8 heterogeneous materials were prepared and used for photocatalytic N2 conversion to nitrate. The enhanced physical and chemical adsorption of N2 molecules resulting from ZIF‐8 contribute to the enhancement of photocatalytical N2 conversion efficiency.